Current status of venous thromboembolism development during the perioperative period for colorectal cancer, its prevention with enoxaparin, and monitoring methods - Aoki J; Sakamoto K; Takahashi R; Niwa K; Ishiyama S; Sugimoto K; Kamiyama H; Takahashi M; Kojima Y; Goto M; Tomiki Y; Iba T (Dove Medical Press, 2019)
Jun Aoki,1 Kazuhiro Sakamoto,1 Rina Takahashi,1 Koichiro Niwa,1 Shun Ishiyama,1 Kiichi Sugimoto,1 Hirohiko Kamiyama,1 Makoto Takahashi,1 Yutaka Kojima,1 Michitoshi Goto,1 Yuichi Tomiki,1 Toshiaki Iba21Department of Coloproctological Surgery, Juntendo University, Faculty of Medicine, Tokyo, Japan; 2Department of Emergency and Disaster Medicine, Juntendo University, Faculty of Medicine, Tokyo, JapanBackground: There is a high incidence of venous thromboembolism (VTE) during the perioperative period for cancer. Therefore, there is an urgent need to elucidate the perioperative onset and appropriate prophylaxis for VTE.Purpose: VTE during the perioperative period for colorectal cancer was evaluated by lower limb venous ultrasonic examinations (lower limb echo) under enoxaparin prophylaxis. We also examined the relationship between hemorrhagic adverse events and anti-Xa factor activity.Patients and methods: Eighty-three subjects who underwent lower limb echo during the perioperative period for colorectal cancer were prospectively included. Enoxaparin was administered for 5 days, from day 1 to day 5 after surgery. Lower limb echo was performed before surgery and on day 5 after surgery. The activated partial thromboplastin time, D-dimer levels, and anti-Xa factor activity were measured before surgery and on days 1, 3, 5, 7, and 9 after surgery.Results: VTEs before surgery were observed on lower limb echo for 16 patients (19.2%). Three patients (3.6%) had a new thrombus during the perioperative period. The preoperative D-dimer level was an independent prognostic factor for newly formed postoperative VTEs (p=0.0036; odds ratio, 19.37). Three patients (3.6%) had hemorrhagic events; however, there was no significant trend for anti-Xa factor activity.Conclusion: VTE prevention using enoxaparin was relatively safe, and D-dimer measurements before surgery were useful for predicting perioperative VTE.Keywords: postoperative complications, pulmonary thromboembolism, deep vein thrombosis, D-dimer, anti-Xa factor activity